Interpretasi Karel A. Steenbrink terhadap Al-Masih - Rani Hasibuan (Jurnal El-Thawalib, 2021)
The Qur'an is the first source of Islamic law that was revealed to the prophet Muhammad SAW. However, the Qur'an is also not only the object of study by Muslim scientists, many non-Muslims also study the Qur'an such as Western scientists and they are said to be Orientalists. One of them is Karel A. Steenbrink who studies the relationship between Jesus AS and the God they believe in today, while Jesus AS is considered by Muslims only as an apostle and messenger of Allah SWT. In understanding this difference Karel refers to the verses of the Qur'an and gives a positive attitude and outlook, unlike other Christians. The formulation of the problem of the author is how Karel A. Steenbrink's attitude and views towards Isa Al-Masih and towards Isa Al-Masih's verses. The aim is to find out the attitudes and views of Karel A. Steenbrink towards Isa Al-Masih and the verses of Isa Al-Masih. The type of research used by the author is library research. The results of this study indicate that Karel A. Steenbrink does not blame and refute the Muslim understanding of Isa Al-Masih who is considered only a creature created by God who is made as a prophet as well as His apostle, while in the Christian understanding of the prophet Isa Al-Masih is a figure of God. known as Jesus Christ, the son of Mary. Karel also believes that the explanation of the verses about Isa Al-Masih has almost the same similarities, such as the process of the birth of Isa Al-Masih in the Qur'an and Christian books.